SAT0702 Influence of obesity and gender on drug effectiveness in rheumatoid arthritis depends on the outcome considered. (12th June 2018) - Schäfer, M.; Meissner, Y.; Kekow, J.; Berger, S.; Remstedt, S.; Strangfeld, A.; Listing, J.; Zink, A.
Abstract : Background: While effectiveness of TNF inhibitors (TNFi) and, to some extent, tocilizumab (TOC), has been shown to be affected by obesity in patients with rheumatoid arthritis (RA), no such effect has been found for abatacept (ABA) and rituximab (RTX). Also, it remains unresolved whether gender is an effect modifier for obesity, e.g. due to different body fat distributions in men and women. Objectives: Assess whether obesity affects drug effectiveness of common DMARDs, taking into account potential differences between sexes. As measures for effectiveness, the degree of improvement regarding DAS28-CRP as well as its components after 6 months of treatment were considered. Methods: Data of 8, 623 RA patients included since 2009 in the German observational cohort study RABBIT were analysed. Patients had to have a BMI ≥18.5 and at least 6 months of follow-up. Multiple imputation of missing values in outcomes was performed. The influence of obesity (BMI ≥30) on drug effectiveness was investigated by multiple linear regression, adjusting for age, baseline value of the outcome of interest, disease duration, prior bDMARD failure, glucocorticoid therapy, number of comorbidities, joint erosions, autoantibody status, and smoking habits. Results: At baseline, obese patients were comparable to others in age (both mean 58 years) and gender (women: 75% vs. 74%). They were less likely to be seropositive (66% vs. 75%), had less erosions (40% vs. 52%) but more often ≥3 comorbidities (43% vs. 30%). With the exception of infliximab, around 90% of patients or more received the recommended drug dosage regardless of their weight (assuming a tolerance interval for norm in case of weight-dependent infliximab and tocilizumab dosages). For women treated with TNFi or csDMARDs as well as for patients treated with TOC, obesity had a negative influence on the improvement in DAS28-CRP after 6 months of treatment (figure 1). With the exception of patients treated with TOC, this influence seemed to be caused mostly by inflammation, while for joint swelling or pain no associations were observed. Men and women treated with TNFi differed significantly regarding the effect of obesity on the improvement of log(CRP) values. Conclusions: The influence of obesity on drug effectiveness depends on the considered outcome and, to some extent, on gender. It may therefore be worthwhile to assess it separately for men and women. Acknowledgements: This abstract is part of the METARTHROS cooperation funded by the German Federal Ministry of Education and Research (01EC1407D). Disclosure of Interest: M. Schäfer: None declared, Y. Meissner Speakers bureau: Pfizer, J. Kekow: None declared, S. Berger: None declared, S. Remstedt Speakers bureau: AbbVie, Biogen, BMS, Celgene, Chugai, Hexal, Janssen Biologics, MSD, Novartis, Pfizer, Roche, Sanofi-Aventis, UCB, A. Strangfeld Speakers bureau: AbbVie, BMS, Lilly, MSD, Pfizer, Roche, UCB, J. Listing: None declared, A. Zink Speakers bureau: BMS, Lilly, Pfizer, Roche, UCB